HenDi-WebApp v6.1.0 - Ried, Dennis

»Play it again, Sam« – Levels of Complexity in Encoding Performance Personnel - Bohl, Benjamin W.; Ried, Dennis (Music Encoding Conference Proceedings 2022)

HenDi-ODD v2.0.0 - Ried, Dennis; Capelle, Irmlind; Minetti, Elena

HenDi-WebApp v1.0.0 - Ried, Dennis

HenDi-ODD v1.0.0 - Ried, Dennis; Capelle, Irmlind; Minetti, Elena

HenDi-WebApp v2.0.0 - Ried, Dennis

HenDi-Data (data package) v2.0.0 - Capelle, Irmlind; Minetti, Elena; Ried, Dennis; Tumat, Antje
This is the data set of the project Henze-Digital. It contains project specific authority files (e.g., persons, organizations, places) and editions (e.g., letters, documents).

HenDi-Data (data package) v1.0.0 - Capelle, Irmlind; Minetti, Elena; Ried, Dennis; Tumat, Antje
This is the data set of the project Henze-Digital. It contains project specific authority files (e.g., persons, organizations, places) and editions (e.g., letters, documents).

METAdata and metaDATA - Ried, Dennis; Gubsch, Clemens
Metadata are a very broad and extremely differentiated subject and ranges from rudimentary catalog data to deeply indexed scientific catalogs (e.g., catalogs of works). In this paper, the concept of metadata in the context of MEI is first examined, before two examples are used to show that metadata are more than just rudimentary descriptions. These examples are also intended to illustrate the extent to which metadata are encoded in the field of music philology and thus represent an attempt to create a little more awareness for the work of the Metadata and Cataloging Interest Group of MEI. The examples deal on the one hand with the encoding of performance resources and on the other hand with watermarks. In both cases, the possibilities of metadata encoding with MEI version 4 are exhausted and it is discussed which steps are useful and necessary to create an even deeper, machine-readable structure so that these sub-fields of the MEI metadata can also be used for larger scientific purposes such as analyses.